Measurement of the branching fractions of doubly Cabibbo-suppressed D decays - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Journal of High Energy Physics)
Abstract By analyzing e + e − collision data collected at the center-of-mass energy of 3.773 GeV with the BESIII detector, corresponding to an integrated luminosity of 20.3 fb −1, we measure the branching fractions of the doubly Cabibbo-suppressed (DCS) decays D 0 → K + π − , D 0 → K + π − π − π +, D 0 → K + π − π 0, D 0 → K + π − π 0 π 0, D + → K + π + π − , and D + → K + K + K − . We also perform the first searches for D 0 → K + π − η, D 0 → K + π − π 0 η, D + → K + π + π − η, D + → K + (π + π − η)non−η′, and D + → K + ηη and report the first observations and evidence for some of these final states. Combining the measurements with the world averages of the corresponding Cabibbo-favored (CF) decays, the ratios of the DCS/CF branching fractions are obtained. For the D + → K + (π + π − η)non−η′ decay, the ratio is significantly larger than the corresponding ratios of the other DCS decays.